Black girlhood, punishment, and resistance : reimagining justice for black girls in Virginia - Battle, Nishaun T. (New York, NY : Routledge, 2019)
"Black Girlhood, Resistance, and Punishment: Reimagining Justice for Black Girls in Virginia provides a historical comprehensive examination of racialized, classed, and gendered punishment of Black girls in Virginia during the early twentieth century. It looks at the ways in which the court system punished Black girls based upon societal accepted norms of punishment of Black girls, hinged on a notion that they were to be viewed and treated as adults within the criminal legal system. Further, the book explores the role of Black Club women and girls, as agents of resistance against injustice by shaping a social justice framework and praxis for Black girls, by examining the establishment of the Virginia Industrial School for Colored Girls. This school was established by the Virginia State Federation of Black Women's Clubs and its first President, Janie Porter Barrett. This book advances contemporary criminological understanding of punishment by locating the historical origins of an environment normalizing unequal justice. It draws from a specific focus on Janie Porter Barrett and the Virginia Industrial School for Colored Girls; a groundbreaking court case of the first female to be executed in Virginia; historical newspapers; and Black Women's Club archives to highlight the complexities of Black girls' experiences within the criminal justice system and spaces created to promote social justice for these girls. The historical approach unearths the justice system's role in crafting the pervasive devaluation of Black girlhood through racialized, gendered, and economic-based punishment. Secondly, it offers insight into the ways in which, historically, Black women have contributed to what the book conceptualizes as "resistance criminology," offering policy implications for transformative social and legal justice for Black girls and girls of color impacted by violence and punishment. Lastly, it offers a lens to explore Black girl resistance strategies, through the lens of the Black Girlhood Justice framework. Black Girlhood, Resistance, and Punishment uses a historical intersectionality framework to provide a comprehensive overview of cultural, socioeconomic, and legal infrastructures as they relate to the punishment of Black girls. The research illustrates how the presumption of guilt of Black people shaped the ways that punishment and the creation of deviant Black female identities were legally sanctioned. It is essential reading for academics and students researching and studying crime, criminal justice, theoretical criminology, women's studies, Black girlhood studies, history, gender, race, and socioeconomic class. It is also intended for social justice organizations, community leaders, and activists engaged in promoting social and legal justice for the youth"--
OCLC-licensed vendor bibliographic record.
Keywords: African American juvenile delinquents -- Virginia -- History -- 20th century; Female juvenile delinquents -- Virginia -- History -- 20th century; Juvenile corrections -- Virginia -- History -- 20th century; Discrimination in criminal justice administration -- Virginia -- History -- 20th century; African American girls -- Virginia -- Social conditions -- 20th century; SOCIAL SCIENCE / Criminology